Staged feminizing genitoplasty with total urogenital sinus mobilization - Fatih Akbiyik (Journal of Surgery and Surgical Research - Peertechz Publications, 2022)
Background: The diagnosis and treatment of individuals with Disorders of Sexual Development is a complex process and requires a multidisciplinary approach. Each individual should be evaluated objectively and the treatment process of each individual has its own unique differences. The aim of this study is to discuss the effectiveness of staged feminizing genitoplasty operations using the total urogenital mobilization technique. Material and methods: Hospital records of patients who underwent vaginoplasty using the TUM technique between 2014 and 2019 by a single surgeon in a pediatric surgery center of a tertiary pediatric hospital were retrospectively reviewed. Results: All ten patients who underwent TUM had 46 XX chromosomes. The TUM procedure for vaginoplasty was performed in all patients by the author. A clitorolabioplasty had been previously performed in six patients with congenital adrenal hyperplasia. The follow-up period of the patients was 1-6 years. No serious complications developed in any of the patients. Neither infection nor tissue necrosis occurred. A second surgical procedure was not required for urinary fistula, vaginal stenosis, urinary incontinence, or early suture dehiscence. Conclusion: This study shows that vaginoplasty can be performed in a single session in infancy for patients with low confluence and a short Urogenital Sinus (UGS). Apart from this, postponing vaginoplasty surgeries to the adolescence period and performing UGS mobilization surgery seem to carry successful results.